Resistance Discourse against Gender Discrimination in MS. Magazine: A Critical Discourse Analysis Study - Annisa Nurfitriani; Andi Muhammad Irawan (Universitas Negeri Padang, 2023)
This research analyzed resistance against gender discrimination in a US-based feminist magazine, Ms., by using Critical Discourse Analysis (CDA). This research aimed to find the discourse topics and discourse strategies in selected news and opinion articles published by Ms. and to reveal how the feminist magazine resist gender discrimination and try to make a change in society based on their ideology through discourse. This study focused in examining how the writers of the articles and Ms. as a feminist media present themselves and other groups based on their ideology. This researcher used qualitative method and employed positive self and negative-other presentation in van Djik’s Ideological Square (2000) as the theoretical framework to analyze the data. From the selected articles, the researcher collected 188 data. Nine discourse topics and 22 discourse strategies were found in the data. The findings of this research reveal that the topics discussed in the selected articles were not only limited on gender issues but also included racism and democracy issues. Moreover, various discourse strategies were used the selected articles to convey negative presentation towards the out-groups (e.g. patriarchy, authoritarianism, corporate media) and positive self-presentation towards the in-groups (e.g. feminism, women, feminist media).